2011
DOI: 10.1016/j.neuroimage.2010.10.071
|View full text |Cite
|
Sign up to set email alerts
|

Improving contrast to noise ratio of resonance frequency contrast images (phase images) using balanced steady-state free precession

Abstract: Recent MRI studies have exploited subtle magnetic susceptibility differences between brain tissues to improve anatomical contrast and resolution. These susceptibility differences lead to resonance frequency shifts which can be visualized by reconstructing the signal phase in conventional gradient echo (GRE) acquisition techniques. In this work, a method is proposed to improve the contrast to noise ratio per unit time (CNR efficiency) of anatomical MRI based on resonance frequency contrast. The method, based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 57 publications
2
16
0
Order By: Relevance
“…This suggests that the local B 0 field reflects underlying architecture and complements the anatomic information from water peak height images, which is consistent with previously published studies performed using T 2 * -weighted images, phase sensitive images, and susceptibility weighted imaging (SWI). [14][15][16][17][18][19][20][21] Interestingly, Figs. 4(e) and 4(f) show a relative frequency inversion and frequency convergence between the labeled layers, respectively (the unlabeled single and double headed line arrows), that corresponds to a change in orientation of the axons in the granular cell layer; specifically, the axons become oriented perpendicular to B 0 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This suggests that the local B 0 field reflects underlying architecture and complements the anatomic information from water peak height images, which is consistent with previously published studies performed using T 2 * -weighted images, phase sensitive images, and susceptibility weighted imaging (SWI). [14][15][16][17][18][19][20][21] Interestingly, Figs. 4(e) and 4(f) show a relative frequency inversion and frequency convergence between the labeled layers, respectively (the unlabeled single and double headed line arrows), that corresponds to a change in orientation of the axons in the granular cell layer; specifically, the axons become oriented perpendicular to B 0 .…”
Section: Discussionmentioning
confidence: 97%
“…Extensions of T 2 * -weighting, often referred to as "phase sensitive" imaging or "susceptibility-weighted imaging," have further increased sensitivity to local susceptibility gradients, thereby providing exceptional anatomic detail. [14][15][16][17][18][19][20][21] Such methods are often used for both in vivo and ex vivo imaging.…”
Section: Introductionmentioning
confidence: 99%
“…We have demonstrated that this sequence allows superior depiction of the medial temporal lobe and cortical microstructure such as the line of Gennari, and it rivals typical iron-sensitive multi-echo GRE for deep brain iron-containing nuclei. Extensive prior efforts at high-field imaging have shown the line of Gennari, but most of these were not isotropic whole-brain imaging protocols that yielded contrast useful for multiple brain regions [21, 37]. The benefit of bSSFP likely stems from the coupling of ultra-high resolution with iron sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, bSSFP demonstrates iron-sensitivity [19] and is an efficient sequence with a high intrinsic signal-to-noise ratio (SNR) [20]. At 7T, phase-imaging with bSSFP has demonstrated SNR benefits compared to GRE per unit imaging time [21]. While bSSFP suffers from bands of signal hypointensity due to B0 inhomogeneity, these can be remedied by phase cycling [22, 23].…”
Section: Introductionmentioning
confidence: 99%
“…In most of these bSSFP studies magnitude imaging has been used, and phase imaging has not been investigated well. The feasibility of phase imaging with transition‐band bSSFP was investigated in a recent study . By using the steep phase changes in the transition bands of bSSFP, the study successfully visualized refined in vivo anatomy with a better contrast to noise ratio (CNR) per unit time than that of GRE.…”
Section: Introductionmentioning
confidence: 99%